What influences online reviews' perceived information quality?: Perspectives on information richness, emotional polarity and product type. Issue 2 (31st March 2020) - Zhu, Linlin; Li, He; He, Wu; Hong, Chuang
Abstract : Purpose: Online reviews presented in the format of multimedia information, such as pictures and videos, continue to emerge, but whether the richness of multimedia information can enforce the quality of online reviews has remained uncertain. The purpose of this paper is to examine the differences in the perceived information quality of online reviews, based on the information richness theory, emotional polarity and product type. Design/methodology/approach: This is a Web-based experiment in which 12 groups constructed at different levels of these three factors were designed for the purpose of obtaining data. Findings: The study results show that under different positive and negative emotional polarities, different information richness and product types have different effects on perceived information quality; for different product types, positive and negative emotional polarity have different effects on perceived information quality. For "search" products, the perceived information quality of online reviews with low information richness is high; under different information richness, different emotional polarity and product types have different effects on perceived information quality. Practical implications: This paper has important practical significance for the management of e-commerce platforms for online reviews. Originality/value: This paper on the perceived information quality of online reviews puts more focus on the formal features of online reviews and aims to discover the relationships between different directions for perceived information quality under the impact of interaction of formats, emotional polarity and product type. The study hopes to further strengthen the application of the information richness theory in the field of online reviews research and to measure perceived information quality from a variety of aspects.